PRODUKSI TANNASE MENGGUNAKAN Aspergillus niger DALAM MEDIA LIMBAH KULIT BUAH KOPI - . Giyarto (JURNAL AGROTEKNOLOGI, 2010)
The presence of recalcitrant and toxic compounds such as caffeine, tannins and polyphenols limit the use of coffee pulp cherries and can cause seriuos environmental contamination. Tannins could be breakdown by tannase. The fungal tannase was produced from coffee pulp cherries using Aspergillus niger, which is applications of the solid state fermentation (SSF) system. The aim of the research was to produce the extracellular fungal tannase from coffee pulp cherries by Aspergillus niger. The result showed that gallic acid formed as result of tannin degradation by Aspergillus niger activity on SSF. The best tannase production was occurred at the time fermentation between 4 to 6 days, that indicated by the enzyme activity 0.189 – 0.211 μmol of gallic acid ml-1 minute-1, gallic acid content of 0.1004 – 0.1121 gL-1, pH of 4.45 – 5.01, and protein content of 2.367 – 2.733 gL-1 .Keywords: Aspergillus niger, coffee pulp cherries, extracellular fungaltannase, gallic acid, solid state fermentation,